2018
DOI: 10.1152/jn.00860.2017
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory electrical stimulation improves skill acquisition, consolidation, and transfer by increasing sensorimotor activity and connectivity

Abstract: The interaction between the somatosensory and motor systems is important for normal human motor function and learning. Enhancing somatosensory input using somatosensory electrical stimulation (SES) can increase motor performance, but the neuronal mechanisms underlying these effects are largely unknown. With EEG, we examined whether skill acquisition, consolidation, and interlimb transfer after SES was related to increased activity in sensorimotor regions, as assessed by the N30 somatosensory evoked potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 70 publications
1
35
1
Order By: Relevance
“…Despite the tenability of this hypothesis and previous evidence for the effectiveness of SES in stroke, dystonia, and healthy participants [9,10,20], the form of SES used in the present study did not improve KOA patients’ motor function, including self-reported function, or relieve pain as compared to sham stimulation (Figure 2 and Figure 3; Table 1). At least part of the reason may lie in the differences in the neurophysiology of sensory and motor systems in KOA in comparison with stroke patients or healthy individuals.…”
Section: Discussioncontrasting
confidence: 81%
“…Despite the tenability of this hypothesis and previous evidence for the effectiveness of SES in stroke, dystonia, and healthy participants [9,10,20], the form of SES used in the present study did not improve KOA patients’ motor function, including self-reported function, or relieve pain as compared to sham stimulation (Figure 2 and Figure 3; Table 1). At least part of the reason may lie in the differences in the neurophysiology of sensory and motor systems in KOA in comparison with stroke patients or healthy individuals.…”
Section: Discussioncontrasting
confidence: 81%
“…The stimulation parameters chosen in the present study were based on our previous report on spinal cord injury in the rat (30). Several clinical studies applying NMES alone suggested sensorimotor function improvement in stroke patients (62,63) although with stimulation frequencies between 10 and 50 Hz. Further, a report showed that activation at 5 Hz on the cortex did improve stroke patients' motor function (64).…”
Section: Discussionmentioning
confidence: 99%
“…(1) Peripheral nerve stimulation could recruit contralesional and surviving ipsilesional cortical neurons to undergo axonal remodeling and motor map reorganization (14,(65)(66)(67). (2) Peripheral nerve stimulation could affect all types of neural pathways including sensory, motor, proprioceptive, as well as polysynaptic transmission (44,45,63). In this way, future studies should investigate whether median nerve E-stim in this stroke model leads to plastic changes or modulation of structures along the ascending pathway, such as neural modulation in the periaqueductal gray (68).…”
Section: Discussionmentioning
confidence: 99%
“…Still, our results support that the passive somatosensory inputs can affect motor function. The cross-modality plasticity theory suggested that somatosensory stimuli could evoke neural responses to promote motor learning (Ackerley, Borich, Oddo, & Ionta, 2016;Ladda et al, 2014;Ludlow et al, 2008;Nasir et al, 2013;Sanes, 2003;Sanes & Donoghue, 2000;Veldman et al, 2018). Research has shown that the orofacial sensorimotor system is essential for sucking, swallowing, and speech production (Barlow, 1998;Barlow & Bradford, 1996;Barlow & Estep, 2006;Barlow, Lund, Estep, & Kolta, 2010;Barlow & Stumm, 2010;Sessle et al, 2007;Sessle et al, 2005;Smith, 2016).…”
Section: Cross-modality Plasticitymentioning
confidence: 99%